Quality of accounting information: Perception of Brazilian Army accountants - Costa, Júlio Ricardo Rezende da; Leitão, Carla Renata Silva (Research, Society and Development, 2023)
The article aims to verify the perception of Brazilian Army accountants about the quality of accounting information. The methodology involved descriptive research and the use of a questionnaire as a data collection instrument. The universe of the study consists of 85 accountants from the Brazilian Army who participate in a messaging group used to exchange information and accounting experiences that are used in military administration, of which 14 responded to the questionnaire. As a result, there was a predominance of male respondents, aged between 41 and 50 years, with postgraduate degrees and professional experience of over 11 years of service, with the majority having more than 20 years of public service and with experience ranging from 5 to 15 years working in the accounting area. With regard to the respondents' perception of the quality of accounting information, it is concluded that, in general, they demonstrated agreement with the existence of qualitative attributes of accounting information within the scope of the Brazilian Army.